Life cycle assessment and synergistic effects of sustainable strategies to improve environmental sustainability in arid climates - Mahdi Keikha; Abdullah Darzi-Naftchali; Ali Motevali; Mohammad Valipour (Results in Engineering)
Adapting sowing date (SD) based on environmental sustainability and increasing productivity is crucial for creating flexibility in agriculture and maintaining food security. This study aimed to optimize SD and nitrogen (N) management using environmental indices in an arid climate. Yield, N use efficiency (NUE), water productivity (WP), and total environmental impact (EI) were assessed for five SDs for barley and triticale crops, along with three levels of N fertilizer application. The AquaCrop model was used for crop yield prediction, and EI was evaluated using Life Cycle Assessment (LCA). Delayed SD led to a shorter growing period (10.6–12.8 %), decreased WP (76.4–87.5 %), and decreased yield (58.3–87.6 %) for both crops compared to conventional SD. In contrast, earlier SD resulted in an extended growing period (1.7–3.6 %), increased WP (14.8–20.4 %), and increased yield (8.3–10.2 %). NUE showed an inverse relationship with increasing fertilizer levels. The most significant EIs were due to N consumption (33.4 %), followed by diesel (28.5 %) and potassium fertilizer (13.7 %) for both crops. Early SD could reduce EI by an average of 12.5 %. Combining early SD with moderate N levels was the most sustainable approach to maximize yield, minimize water use, and reduce EI, thereby informing sustainable practices for cereal cultivation in similar climates.